LoRa Communications in Wireless Sensor Network for Radioactive Sources Monitoring System - Vinh, Tran-Quang; Kieu-Ha, Phung; Kien, Hoang Trung; Dung, Mai Van; Dao, Quang Thuan (Old Journal, 2019)
Using LoRa, a low-power long-distance communication technology, for wireless sensor networks (WSNs) that have limited coverage range can extend to kilometers, much longer than other technologies such as Zigbee, WiFi, WiSUN, while maintaining the sensor node’s energy consumption at a relatively low level. In this paper, the authors present the architecture of wireless sensor network systems used to monitor radiation sources. The system consists of sensor nodes integrated with radioactive sensors and linked together to form a radioactive network monitoring system. The LoRa is used to transmit data between sensor nodes and sink. Also in this paper, authors propose to use the MAC multi-access protocol specifically designed for communication between nodes in the radiation control system, ensuring reliable transmission requirements and advantages of energy consumption for communication function. Experimental implementation results show that the system can work well with transmission range of up to 2 km in urban environments.